Penyuluhan Bahaya Merokok pada Remaja di MAN Insan Cendekia Kota Kendari - Paridah; Sella Febrina; Bahar, Hartati; Muchtar, Febriana; Savitri Effendy , Devi; Lestari, Hariati; Tosepu, Ramadhan (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
In Indonesia, smoking rates in the 10 to 18 year age group have increased. Based on Basic Health Survey (Riskesdas) data, it shows that the proportion of teenage smokers increased from 7.2 percent in 2018 to 9.1 percent in 2019. This outreach aims to provide education to teenage students at MAN Insan Cendekia Kendari City in an effort to increase understanding about dangers of smoking in teenagers. The methods used are, education about the dangers of smoking in the form of material about understanding smoking behavior, government efforts to reduce smoking behavior, the dangers of active and passive smoking, data on smoking behavior of the population aged 10-18 years, the role of health promotion in controlling smoking behavior and introducing HOTC ( Halu Oleo Tobacco Control Center) using PPT media, animated videos and educational games Smart Box: Cigarette Tour's and playing first place quizzes. The results of this education show that the p value is 0.00 < 0.05, so Ho is accepted. Therefore, there is a significant difference between the average pre-test results and post-test results. Thus, it can be concluded that there is a difference in knowledge before and after being given counseling on the dangers of smoking to teenagers at MAN Insan Cendekia, Kendari City